El monacato y la cristianización del NO hispano: Un proceso de aculturación - Díaz Martínez, Pablo de la Cruz (Antigüedad y cristianismo: Revista de Estudios sobre Antigüedad Tardía, 1990)
The present work aspires to explain in what way the monastic institutionalization was the vehicle that made possible the definitive, and late, Christinaization of the NW of the Iberian Peninsula. The monasticism was, in essence, a mechanism of organization capable of integrating the traditional peasant way of life with the Christian values. The peasant communities found in the monastic practices the best Christian adaptation with the level of development of their social and economic structures.